2018
DOI: 10.1111/iju.13799
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury and intermediate‐term renal function after clampless partial nephrectomy

Abstract: Objectives To evaluate the incidence and predictors of acute kidney injury after clampless partial nephrectomy, and its impact on intermediate‐term renal function. Methods The incidence and severity of acute kidney injury were assessed for 262 patients undergoing clampless partial nephrectomy between 2010 and 2015. The association between perioperative covariates and acute kidney injury was evaluated using multivariate logistic regression analysis. An annual change in estimated glomerular filtration rate from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Therefore, the impact of AKI after PN on long‐term functional outcomes has been controversial. Previous studies demonstrated that the incidence and severity of AKI did not correlate with long‐term functional recovery after off‐clamp PN, 7 and similar findings were reported in patients who had undergone PN for a solitary kidney 8 . In contrast, several studies have described a positive correlation between AKI and decreased renal function after PN.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, the impact of AKI after PN on long‐term functional outcomes has been controversial. Previous studies demonstrated that the incidence and severity of AKI did not correlate with long‐term functional recovery after off‐clamp PN, 7 and similar findings were reported in patients who had undergone PN for a solitary kidney 8 . In contrast, several studies have described a positive correlation between AKI and decreased renal function after PN.…”
Section: Discussionsupporting
confidence: 53%
“…The study by Kawamura et al . evaluated the incidence of acute kidney injury (AKI) and intermediate‐term renal function after clampless partial nephrectomy (PN) . It showed that 8% of patients in this study experienced grade 1 AKI, whereas grade ≥2 AKI was not observed.…”
mentioning
confidence: 85%
“…The objects were endoscopic images obtained in animal experiments carried out with the approval of the local ethics committee for animal experiments using four specific pathogen-free (SFP) pigs that weighed approximately 30 kg. Laparoscopic non-ischemic partial nephrectomy (27) was performed using the WaFLES technique by two urologists. The non-ischemic partial nephrectomy does not cause ischemia; therefore, although damage to the normal tissue is suppressed, (27) hemostasis is important because bleeding is frequent.…”
Section: Training Dataset and Svm Classifier Verificationmentioning
confidence: 99%
“…Laparoscopic non-ischemic partial nephrectomy (27) was performed using the WaFLES technique by two urologists. The non-ischemic partial nephrectomy does not cause ischemia; therefore, although damage to the normal tissue is suppressed, (27) hemostasis is important because bleeding is frequent. From the obtained endoscopic images, the organ region pixels (206606 pixels), bleeding region pixels (147456 pixels), and hemostasis region pixels (147456 pixels), a total of 501518 pixels, were randomly extracted (Fig.…”
Section: Training Dataset and Svm Classifier Verificationmentioning
confidence: 99%